The Pharisees: their history, character, and new testament portrait - Yinger, Kent L. (Cascade Books, 2022)
Introduction --Part 1:Origin and History of the Pharisees --Josephus and the beginnings of the Pharisees --Josephus and the historical development of the Pharisees --Part 2:Character of the Pharisees --Distinctives in Josephu --Echoes in the DSS and Rabbinic literature --Common identity with other Jews --Part 3:New Testament Portrait: Disagreements with Pharisees --Jesus and the Pharisees: Introductory matters --Never on Saturday: Disagreements over Sabbath rules --Eating with sinners: Dinner with Levi the Toll-Collector --Don't touch that! Eating with unclean hands and other disagreements over purity rules --Who are you? Core disagreements over kingdom, authority, and identity --Political dynamite: Pharisees, politics, and power --Why do you eat so much? Jesus, fasting, and the Pharisees --Part 4:New Testament portrait: Attitudes toward Pharisees --Were the Pharisees legalists? --Woe to you hypocrites --A more positive spin on the Pharisees in Acts and Paul --Taking stock of the Pharisees: Conclusions and suggestions.